Global Stability for Fractional Diffusion Equations in Biological Systems - Khalid Hattaf; Noura Yousfi (Complexity)
This paper proposes a new method of construction of Lyapunov functionals for the dynamical systems described by fractional differential equations and fractional partial differential equations. The proposed method is rigorously presented. Furthermore, the method is applied to establish the global stability of some fractional biological models with and without diffusion.